Saúde, comunicação e ferramentas digitais: movimentos de ensino-aprendizagem mediados pelo podcast - Bastos, Ediane Cristina Albuquerque (Brasil, 2023)
The present study was conceived in order to add efforts to discuss the use of communication technologies in the area of health, from the experience experienced by the multidisciplinary management of Telesaúde, especially to initiatives linked to the Podcast Telehessaúde UFAM. The project performed in podcast format featured the production of UFAM undergraduates and residents of the Multiprofessional Residence Program of the Getúlio Vargas University Hospital (HUGV). 79 episodes were performed, with 4,604 reproductions on Spotify, Apple Podcasts, Anchor and Web Browser. Initially, the intention was to add efforts to confront COVID-19, however, extended to other health-related fronts such as: Unified Health System (SUS), Ministry of Health campaigns, multidisciplinary topics, festive dates, dates and the institutional community. Productions have achieved national spectators and in Germany and United States countries. Male listeners (62.9%), widely age group (18 to 60 years), predominated. Despite the challenges faced, such as restriction measures from the pandemic moment, the difficulty in contacting health professionals and scarce resources for the steps of production and dissemination of episodes, the proposal allowed the interaction between professionals and students, as it enabled the evidence of the challenges that the community experiences daily. In general, the emergence of this discussion finds a depth in the importance of initiatives of this nature, both in favor of approaching specialized health discourse with a more comprehensive audience, as well as by the internal dynamics of labor that is inherent, undeniably timely and healthy for the academic trajectory of those involved. In short, the experience of Podcast Telehealth Ufam enabled, on the one hand, the provision of secure health information, in its most varied subthemes, to the community of listeners, and on the other, learning about the necessary actions to materialize this initiative.